Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1002/ajim.4700050303
|View full text |Cite
|
Sign up to set email alerts
|

Health status of workers with past exposure to 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin in the manufacture of 2,4,5‐trichlorophenoxyacetic acid: Comparison of findings with and without chloracne

Abstract: Chloracne was found in 52% of 226 workers in a 1979 cross-sectional survey at a plant where 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) had been manufactured from 1948 to 1969. Mean duration of residual chloracne was 26 years, and in 29 subjects, it had been present for 30 years. A significant increased prevalence of abnormal gamma-glutamyl transpeptidase (GGT) and higher mean GGT were found in those with chloracne, compared to those without. Although mean triglyceride values were higher in those with chloracn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 54 publications
(18 reference statements)
1
41
0
Order By: Relevance
“…Several cross-sectional medical studies have also examined the association between TCDD exposure and effects on the cardiovascular system (23)(24)(25)(26)(27). Statistically significant associations were found only in the U.S. Air Force Ranch Hands Study (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cross-sectional medical studies have also examined the association between TCDD exposure and effects on the cardiovascular system (23)(24)(25)(26)(27). Statistically significant associations were found only in the U.S. Air Force Ranch Hands Study (27).…”
Section: Methodsmentioning
confidence: 99%
“…Four mortality studies of TCDD-exposed cohorts reported significantly elevated risks for cardiovascular disease mortality (15)(16)(17)(18), whereas several others have not observed such elevations (19)(20)(21)(22). Although several cross-sectional medical studies have also examined the association between TCDD exposure and effects on the cardiovascular system (23)(24)(25)(26)(27), statistically significant associations were found only in the study of U.S. Air Force Ranch Hand personnel responsible for spraying TCDD-contaminated Agent Orange in Vietnam (27). The Ranch Hands Study found statistically significant associations between TCDD exposure and peripheral pulse abnormalities of several arteries, medical record-verified hypertension, and one type of electrocardiogram (ECG) abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Even men with relatively high levels of TCDD exposure, as evidenced by chloracne, demonstrated no increase in fathering infants with congenital malformations or in their wives' having pregnancies that ended in spontaneous abortion (100,111,154). However , these studies are limited by small numbers and by recall of pregnancies up to 30 years previously.…”
Section: Occupational Exposurementioning
confidence: 94%
“…Peripheral neuropathy has been reported following occupational exposure to the phenoxy herbicides , 2,4,5-T and 2,4-D (111,123,145). Neurologic toxic ity has also been noted from acute exposure to pesticides containing arsenic, the fumigant methyl bromide , and rodenticides containing thallium (9, 74, 75, 93).…”
Section: Neurotoxic Hazardsmentioning
confidence: 99%
“…The mean serum GGT levels and the incidence rate of abnormal serum GGT values (greater than 29 International Units [IU]) were also increased in the chloracne group (26.3 IU, 23%) as compared to the nonchloracne cohort (17.4 IU, 9%) (86). Additionally, after accounting for various confounding variables, the incidence rate of upper GI tract ulcers continued to be significantly elevated in the exposed chloracne group versus the referent population (16.6% vs 5.5%).Various neurologic abnormalities (e.g., peripheral-sensory neuropathy, decreased nerve conductance velocity, decreased libido, depression, insomnia) have been observed in humans occupationally or accidentally exposed to PCDDs/PCDFs.…”
Section: Biomarkers Ofexposurementioning
confidence: 99%